A Review on Melanin, Energy, and the Cell - Herrera, A. S. (Highlights on Medicine and Medical Research Vol. 9, 2021)
In the 19th century, researchers first realized that metabolism can be viewed as a network of connected biochemical reactions. Apparently, enzymes catalyze these reactions, accelerating the rate at which they take place; however, our body is not merely a sack of enzymes. Several of the most prevalent diseases in modern society, as diabetes, cardiovascular disease and obesity involve disruptions of metabolic processes. In patients with diabetes mellitus, this results in an excessive amount of glucose in the blood. The first scientific article dating back to the 17th century, until today; almost six million articles have been published about metabolism. In spite, new insights continuously published, providing pieces of the puzzle about the mechanisms of metabolic processes; we cannot understand metabolism if only study the individual parts of the network reactions. It is something like trying to understand the complex functioning of our solar system with isolated photographs from the Moon, the Sun, or the planets. To understand the metabolism, which means continuous change; It is necessary to study the network as an ever-changing whole, including the energy needed. Any change requires energy because energy is defined as everything that produces a change. Therefore, cellular metabolism, involving continuous changes means that it requires the presence of power on a continuous basis. So far, glucose is considered as the energy source par excellence of eukaryote cell. But the models that have been created based on this dogma, have resulted in the creation of databases whose metabolic pathways are controversial by 97%. The lack of consensus between different metabolic pathway databases is substantive and cannot be explained adequately. We think that the discovery of the unsuspected intrinsic capacity of the melanin of transform the light, visible e invisible, in chemical energy by means of the dissociation of the molecule of the water, as the chlorophyll in plants; this is: Producing chemical energy which is carried by the hydrogen (H2). It will bring the appropriate molecular logic to implement more coherent, more consistent metabolic models. The discerning that the true role of glucose is only as a source of carbon chains with which our body synthesizes the biomolecules that needs to operate, to maintain shape; and the light visible and invisible as the true source of power, thanks to the melanin; means the birth of a new biochemistry. The study of the metabolism of the glucose has proven to be a formidable challenge. It is easier to study proteins. But we now understand that the glucose only provides the building blocks of organic molecules but does not provide the energy that requires its own metabolism.